A scoping review of the effects of mushroom and fungus extracts in rodent models of depression and tests of antidepressant activity - Wang, Catherine K.; Kim, Gio; Aleksandrova, Lily R.; Panenka, William J.; Barr, Alasdair M. (Frontiers in Pharmacology, 2024)
One of the most important developments in psychopharmacology in the past decade has been the emergence of novel treatments for mood disorders, such as psilocybin for treatment-resistant depression. Psilocybin is most commonly found in different species of mushroom; however, the literature on mushroom and fungus extracts with potential antidepressant activity extends well beyond just psilocybin-containing mushrooms, and includes both psychedelic and nonpsychedelic species. In the current review, we systematically review the preclinical literature on mushroom and fungus extracts, and their effects of animal models of depression and tests of antidepressant activity. The PICO structure, PRISMA checklist and the Cochrane Handbook for systematic reviews of intervention were used to guide the search strategy. A scoping search was conducted in electronic databases PubMed, CINAHL, Embase and Web of Science. The literature search identified 50 relevant and suitable published studies. These included 19 different species of mushrooms, as well as seven different species of other fungi. Nearly all studies reported antidepressant-like effects of treatment with extracts. Treatments were most commonly delivered orally, in both acute and chronically administered studies to predominantly male rodents. Multiple animal models of depression were used, the most common being unpredictable chronic mild stress, while the tail suspension test and forced swim test were most frequently used as standalone antidepressant screens. Details on each experiment with mushroom and fungus species are discussed in detail, while an evaluation is provided of the strengths and weaknesses of these studies.